Parasitic Contamination of Vegetables from Open Markets and Supermarkets in Thonburi District, Bangkok - เนียมนุ้ย, นันทวดี; สืบแก้ว, รัชนีกร; อักษรเนียม, ณัฐชนน; นิมนากรณ์, วรยา; สายบัวแดง, แพร; พณโสภณกุล, โชติช่วง; เผ่าจินดา, ภัสราวดี (Journal of Health Science of Thailand, 2022)
Vegetables are important sources of essential nutrients for human health. In particular, raw vegetables may be richer in certain nutrients than cooked food. However, raw vegetables have a greater association with foodborne or waterborne parasitic illnesses. This study explores the prevalence of parasite contamination in eight types of raw vegetables. A total of 162 raw vegetable samples were recorded which were purchased from six fresh markets and two supermarkets in Thonburi district, Bangkok. Further, the efficacy of two vegetable washing methods is compared, namely washing in clean water and washing in 0.05% baking soda solution (sodium bicarbonate). The results indicate that 59.9% of the studied vegetables were contaminated with parasites. The highest contamination was observed in sweet basil (92.3%), followed by scallion (85.7%) and celery root (85.7%), respectively. The prevalence rates of parasitic contamination was statistically significant among different types of raw vegetables, with a p<0.001. Although there was no statistically significant difference between the two vegetable washing methods, baking soda solution more effectively reduced the amount of parasite contamination. This study provides basic information useful for the control of foodborne and waterborne pathogenic parasites in raw vegetables for consumption.